Dampak Terapi Murottal Al-Qur’an terhadap Kualitas Tidur - Susanti, Santi; Qomaruzzaman, Bambang; Tamami, Tamami (Jurnal Riset Agama, 2022)
Students have busy activities, this causes students to experience health problems, both physically and psychologically. One way to overcome this problem is to sleep quality by listening to murottal Al-Qur'an therapy. This study aims to determine the murrotal method as Al-Qur'an therapy on sleep quality in students Majoring in Sufism and Psychotherapy class 2018 as well as to determine the impact of murrotal on sleep quality in students majoring in Sufism and Psychotherapy class 2018. The method used in this study was to descriptive qualitative approach, namely observation, literature study, and interviews. The results and discussion in this study show that murottal can be one of the Qur'anic therapies for students who are busy with lectures, so that they have good sleep quality. The conclusion of this study is that murottal Al-Qur'an therapy has a positive impact on sleep quality in students with a method that can be easily done by everyone.